An Audit of Tuberculosis from Sir Ganga Ram Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the prevalence of tuberculosis and its types in patients admitted in Sir Ganga Ram Hospital, Lahore. And to make the patients aware of possible consequences of tuberculosis and protective measures that should be taken.Materials and Methods: A consecutive case series was done among 150 diagnosed tuberculosis patients of age group 14 to 75 years admitted in different medical units of Sir Ganga Ram Hospital, Lahore during a period of three months (from September 2011 to November 2011). Data was collected by interviewing the patients using a self administered questionnaire and also by extracting their history files. Information sought included demographic data, signs and symptoms, and risk factors of TB.Results: A total of 150 patients, majority 79% male participated in the study. About half of the patients were of age group 30-50 years. A large proportion of the patients 81% were illiterate and belong to the lower socioeconomic class. Almost 59% of cases had pulmonary TB, 27% had abdominal TB, 7% had vertebral tuberculosis and 7% had meningeal tuberculosis. Most of the patients 74% were taking anti TB medicine. About 57% of the cases had positive contact history. A vast number of patients 90% had anorexia, majority 91% patients had weight loss, and 80% of the patients experienced fatigue and flu like symptoms were observed in 7% of the patients. Fifty nine percent had high grade fever; in 84% of the patients fever was associated with chills and rigor and accompanied by night sweats in 71% of cases. The pulmonary symptoms of tuberculosis including cough was present in 64%, dyspnea in 53% of the patients, hemoptysis in 48% of cases, and pleuiritic chest pain in 40% of the patients.Conclusion: Tuberculosis is a curable disease but its number is increasing day by day in Pakistan mainly because of illiteracy and poverty and lack of awareness about TB. No necessary steps are being taken to prevent the spread of TB. Even in most of the government hospitals there are no isolated wards available for TB patients. Awareness about the spread, symptomatology, treatment and consequences of TB particularly to the patient and to general population is recommended.
Keywords: Tuberculosis, Recurrent infection, Smoking, Illiteracy, Poverty